Effect of Nitrogen Fertilizer on some Attributes of SorghumGrown in Saline Soil under Irrigation - Haroun M.Adam, Abubaker; Ahmed Taleim, Mohammed (Journal of Agronomy Research, 2018)
The main objective of this study was to investigate the effects of 4 levels of Nitrogen (N) fertilizer (0, 25, 50 and 75 Kg N/fed) on some attributes of Sorghum (Sorghum bicolor L). This study was conducted in the farm of College of Agriculture, University of Bahri-Sudan; during the period 2014-2015. Where the soil is classified as saline with pH ranging from 7.5 -7.8. A randomized completely block designed (RCBD); with 3 replications and four (4) treatments was adopted. All recommended cultural practices were carried out timely. Data; pertaining some plant attributes were collected and analyzed. The result showed that the application of 75KgN/fed has increased both; the average number of leaves as well as the plant height compared to other levels of Nitrogen fertilizer including the control (Figure 1, Figure 2). For the average number of tillers concern, there is non -significant difference between all Nitrogen levels and average number of tillers (Figure 3). The study concluded that the Nitrogen fertilizer has variable effects on the studied agronomic characters, and the application of 75kgN/fed is the optimal level of fertilizer for improving the agronomic traits of Sorghum under Alkadaro conditions.
Keywords: Germination; fertilizer; Kadaro; Parameter